2018
DOI: 10.1002/cem.3081
|View full text |Cite
|
Sign up to set email alerts
|

A method for improvement of mass resolution and isotope accuracy for laser ablation time‐of‐flight mass spectrometers

Abstract: Accumulation of spectra is a common approach for improvement of the signalto-noise ratio (SNR) in mass spectrometry. However, severe degradation of the overall spectrum can occur if some individual mass spectra, affected by peak broadening, are included in the accumulation process. In this contribution, we discuss potential sources and effects of spectral distortions by using examples from mass spectra acquired by our miniature laser ablation/ionisation time-of-flight mass spectrometer. We show how recent deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Mass calibration of the spectra, mass peak integration, and the spectra filtering procedure were discussed in details in our previous publications. 23,[35][36][37]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass calibration of the spectra, mass peak integration, and the spectra filtering procedure were discussed in details in our previous publications. 23,[35][36][37]…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we developed a spectrum filtering software that allows for the identification and removal of the distorted mass spectra following a well-defined procedure. 37 Using a score function that describes the spectral quality based on selected mass peaks, spectra of bad quality are identified and removed from the analysis. The remaining mass spectra are subsequently used for further analysis.…”
Section: Data Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative sensitivity coefficients close to one, a pre-requisite for standard-less quantitative analysis, became feasible 14,66,67 . It was also demonstrated that detection limits in the sub-ppm range are nowadays possible 14,68 .…”
Section: Quantificationmentioning
confidence: 99%
“…The measured mass resolution gradually reaches a plateau at m/∆m ≈ 8000 for the accumulation of 20 mass spectra and at m/∆m ≈ 9000 for the accumulation of 20'000 mass spectra. This difference can be explained by the effect of the initial crater formation process during which the laser ablation process is less stable 68 . In the second case more spectra are recorded under stable ablation conditions, which results in increased mass resolution.…”
Section: Comparison Of Simulation To Measurementmentioning
confidence: 99%